Determination Of Bod Kinetic Parameters For Different Wastewater By Using Different Mathematical Model - Al-Rousan, Doua’a A. (2019)
One of the most important parameter of the wastewater quality is biochemical oxygen demand (BOD). This test is widely applied to define organic water pollution and to control the performance of wastewater treatment plants and to identify the suitable places that can be used the wastewater after treatment. In order to estimate the total organic matter (BODu), understanding the organic strength of the wastewater and to predict the impacts of wastewater discharging after treating, determination of ultimate BOD (BODu) and reaction rate constants (K) are crucial. In this study, the best BOD kinetics parameters (BODu, K) for 5 different sources of wastewater (influent, effluent and aeration for Al-Ramtha wastewater, Amman slaughterhouse and Alomary dairy factory wastewater) in Jordan are investigated comparatively. The BOD kinetics parameters are estimated by using least squares, Thomas, daily difference, iteration, generalized method of moments, and two stage square methods. The study revealed that the BOD kinetic parameters (L0 and K) of the raw wastewater are the highest for slaughterhouse samples in 2017 and 2018, in which the ultimate BOD values are 922, 1042 mg/L and the BOD rate constants are 0.553, 0.149 d-1 respectively in two years. The finding suggests that the result of characteristics for Al-Ramtha treatment plant is classified as a strongest wastewater in Jordan. The range of average values of ultimate BOD (L0) and constant rate (K) are from 392 to 819 mg/L and 0.126 to 0.417 d-1 respectively. In addition, based on the relative error (RE), GMM and two stage square methods are the best method for estimating BOD kinetic parameters, where the ratio of errors varies from 0.13 to 0.31 for two years.